Nucleolin-Targeting AS1411 Aptamer-Modified Micelle for the Co-Delivery of Doxorubicin and miR-519c to Improve the Therapeutic Efficacy in Hepatocellular Carcinoma Treatment - Liang X (Dove Medical Press, 2021)
Xiao Liang,* Yudi Wang,* Hui Shi, Mengmeng Dong, Haobo Han, Quanshun Li Key Laboratory for Molecular Enzymology and Engineering of Ministry of Education, School of Life Sciences, Jilin University, Changchun, 130012, People’s Republic of China*These authors contributed equally to this workCorrespondence: Quanshun Li; Haobo Han Tel/ Fax +86-431-85155200Email quanshun@jlu.edu.cn; hanhaobo@jlu.edu.cnBackground: Multidrug resistance (MDR) has emerged to be a major hindrance in cancer therapy, which contributes to the reduced sensitivity of cancer cells toward chemotherapeutic drugs mainly owing to the over-expression of drug efflux transporters. The combination of gene therapy and chemotherapy has been considered as a potential approach to improve the anti-cancer efficacy by reversing the MDR effect.Materials and Methods: The AS1411 aptamer-functionalized micelles were constructed through an emulsion/solvent evaporation strategy for the simultaneous co-delivery of doxorubicin and miR-519c. The therapeutic efficacy and related mechanism of micelles were explored based on the in vitro and in vivo active targeting ability and the suppression of MDR, using hepatocellular carcinoma cell line HepG2 as a model.Results: The micelle was demonstrated to possess favorable cellular uptake and tumor penetration ability by specifically recognizing the nucleolin in an AS1411 aptamer-dependent manner. Further, the intracellular accumulation of doxorubicin was significantly improved due to the suppression of ABCG2-mediated drug efflux by miR-519c, resulting in the efficient inhibition of tumor growth.Conclusion: The micelle-mediated co-delivery of doxorubicin and miR-519c provided a promising strategy to obtain ideal anti-cancer efficacy through the active targeting function and the reversion of MDR.Keywords: micelle, aptamer, nucleolin, multidrug resistance, tumor targeting